Multilevel botulinum toxin type a as a treatment for spasticity in children with cerebral palsy: a retrospective study - Ece Unlu; Alev Cevikol; Burcu Bal; Emel Gonen; Ozlem Celik; Gulşen Kose (Clinics, 2010)
INTRODUCTION: Cerebral palsy is the most common cause of physical disability in children. Spasticity is a disabling clinical symptom that is prevalent among patients suffering from cerebral palsy. The treatment of spasticity with botulinum toxin type A (BTX-A) is a well-established option in the interdisciplinary management of spasticity, providing focal reductions in muscle tone in cerebral palsy patients. OBJECTIVE: The aim of this retrospective study was to describe the effect of multilevel BTX-A injections in the lower extremities, focusing mainly on gross motor function and functional status in cerebral palsy patients. METHODS: Data from 71 cerebral palsy patients (64% male, 36% female, mean age 6.7 ±3.2 years) were analyzed retrospectively. We used the Ashworth and Tardieu scales to evaluate the degree of spasticity. Motor function was measured by the Gross Motor Function Measure (GMFM-88), and functional status was classified by the Gross Motor Function Classification System (GMFCS I-V). Multilevel BTX-A injections were applied after sedation and with electrostimulation guidance. The evaluations were repeated every three months, and the patients were followed for six months. RESULTS: We found that the Ashworth and Tardieu scores decreased significantly at the three-month evaluation (p<0.05) but not at the six-month evaluation (p>0.05). Although the improvement in spasticity was not maintained at the six-month evaluation, GMFM-88 scores increased significantly at the three- and six-month assessments. GMFSC levels showed no change in the three- and six-month assessments. CONCLUSION: We believe that a single multilevel BTX-A injection reduces spasticity and improves motor function in children with cerebral palsy.